The effect of commercial liquid smoke immersion on tofu storage period - Akilie, Muhammad Sudirman; Xyzquolyna, Deyvie; Gobel, Muh. Rifki (Anjoro: International Journal of Agriculture and Business, 2021)
The study aimed to analyze the effect of commercial liquid smoke immersion on tofu production for 3 hours with chemical characteristics indicated such as water content, ash content, total microbes, and organoleptic test. The method used in this study is Completely Randomized Design with four treatments for 0, 3, 5, and 7-days storage using 0.5% of commercial liquid smoke. The ANOVA statistics indicates that three hours tofu immersion in liquid smoke significantly impacts on water content and ash content for 0, 3, 5, and 7-days storage. There was a significant increase of total microbes during storage period. The best treatment based on organoleptic test covering flavor, color, and texture was the treatment with 0 day tofu storage period.